Iconographic Analysis of Goddess Chinnamasta: Unveiling Divine Power of Mahavidhya in Hindu Mythology - Bishnu Prasad Pokharel,; Sultana Banu, (Butwal Campus Journal, 2024)
The paper discusses the iconographic analyses and symbolic interpretation of Goddess Chinnamasta, whose headless body is the crux of supreme power and revelation of one of the ten forms of Mahavidya Hindu mythology. Through the iconographical analysis of the Chinnamasta, the paper analyses the ideas of a body without an organ in connection with the supreme power of the female Goddess as Shakti in Hindu mythology. Using symbolic interpretation grounded in Hindu tantric theory and gender insights as the study methodology. It studies the process of reaching the super soul from tantric perspectives. The paper employs the concepts of the Tantra by Kinsley and Flood, and Butler’s gender identity, as analytical tools to examine the claim. Ultimately, the study deduces that the iconography of the Goddess reflects two distinct yet interconnected aspects of the body: the head and body. The head symbolizes symbolic power, whereas the body represents physical power. Together, they work as a whole for two distinct roles: creator and destroyer. The separate forms signify distinct entities, encompassing their function and the notion of transcending the self to unite with the supreme soul through the self-denial of personal value in pursuit of ultimate power. Therefore, this extends Chinnamasta’s iconography as the body devoid of organs, relating to the entirety of the body in the context of supreme power.